Rozwiązane

Wyznacz sumę rozwiązań nierównań
(x²-3)(x²+25)(x³-64)(2x+8)=0



Odpowiedź :

Odpowiedź:

Szczegółowe wyjaśnienie:

[tex](x^2-3)(x^2+25)(x^3-64)(2x+8)=0\\(x-\sqrt{3} )(x+\sqrt{3})(x^2+25)(x-4)(x^2+4x+16)(2x+8)=0\\[/tex]

      |               |              \              \                    \                  \

      |               |                \                   \                  \                  \

[tex]x_1=\sqrt{3}[/tex] v [tex]x_2=-\sqrt{3}[/tex] v brak rozwiązań v [tex]x_3=4[/tex] v brak rozwiązań v [tex]x_4=-4[/tex]

[tex]\sqrt{3} -\sqrt{3} +4-4=0[/tex]